Integrable CMOS-Based Current-Mode Sinusoidal Frequency and Peak Detector - Prommee, Pipat (My University, 2017)
This research proposes the integrable CMOS current-mode instantaneous frequency and peak detector (FPD) based on the trigonometric relationships and mathematic algorithm without the divider function and low-pass filter. The proposed FPD structure is straightforward, consisting of two differentiators, two multipliers and one square-rooter. The input of FPD is operable in the 20–100 kHz frequency and 20–100 μ A amplitude under ± 1.5 V power supplies. In the research, the FPD was simulated using the current-mode CMOS technology and a prototype detector subsequently materialized using the commercially available components. In addition, the FPD was experimentally utilized as the FM and AM demodulators with very satisfactory demodulation outcomes. The simulation and experimental results were agreeable and also consistent with the trigonometric relationships and algorithmic scheme. More importantly, the integrable FPD could achieve the high-accuracy current output and fast response.
Keywords: CMOS; Frequency detector; Mathematic algorithm; Peak detector; Sinusoidal